[Louis family scrapbook, China trip, 1933] (1933)
Scrapbook with photographs from the Louis' trip to China in 1933. Includes family photographs, photographs on the S.S. President Hoover and photographs of sights and people in Honolulu, Shanghai, Hong Kong and Canton (Guangdong Province).